The impact of the New Rural Cooperative Medical Scheme on the “health poverty alleviation” of rural households in China - Li-jian QIN; Chien-ping CHEN; Yu-heng LI; Yan-ming SUN; Hong CHEN (Journal of Integrative Agriculture)
This study investigates the impact of the New Rural Cooperative Medical Scheme (NRCMS) on rural households to escape poverty. We employ the instrumental variable method, the IVProbit model, to analyze the national data from the rural-resident field survey by the China Family Panel Studies (CFPS) in 2016. Based on the large-scale data, we found that, first, the hospitalization of family members is the key factor in increasing the risk of the family falling into poverty. The NRCMS has significantly reduced the likely risk of falling into poverty. Second, the impact of the NRCMS on poverty alleviation varies among groups with different levels of income. There is no impact on the upper-middle and high-income groups; in contrast, the NRCMS has substantially improved the capacity of low-income rural families to prevent poverty due to illness, especially for the lower-middle-income group. Third, there exist significant regional differences in the impact of NRCMS on the health poverty alleviation of rural households in China. The NRCMS has successfully reduced the risk of rural households in the western region falling into poverty, simultaneously, no significant impact on those in the eastern and central regions. In order to diminish and eliminate poverty eventually and boost rural residents’ capacity for income acquisition, we propose the following: raise the actual compensation ratio of the NRCMS, control the rising expense of NRCMS by promoting the payment method reform, construct the comprehensive healthcare system in the western region, strengthen the medical security for the poor in remote area, and enhance the living environment for rural residents.